Healing Home : Health and Homelessness in the Life Stories of Young Women - Oliver, Vanessa, 1980- (Book collections on Project MUSE., 2013)
Applying a strong, articulate, and systemic analysis to on-the-ground narratives, Oliver is able to offer fresh, incisive recommendations for health and social service providers with the potential to effect real-world change for this marginalized population.